Virtual bronchoscopic navigation versus non-virtual bronchoscopic navigation assisted bronchoscopy for the diagnosis of peripheral pulmonary lesions: a systematic review and meta-analysis. (May 2021) - Giri, Mohan; Puri, Anju; Wang, Ting; Huang, Guichuan; Guo, Shuliang
Background: Image-guided bronchoscopy techniques such as virtual bronchoscopic navigation (VBN) has emerged as a means of assisting in the biopsy of peripheral pulmonary lesions. However, the role of VBN-assisted (VBNA) bronchoscopy in the diagnosing of peripheral pulmonary lesions (PPLs) has not been well established. This meta-analysis investigated the diagnostic yield of VBN-assisted versus non-VBN-assisted (NVBNA) bronchoscopy for PPLs. Methods: PubMed, Embase, Cochrane library, and Web of Sciences databases were searched up to and including August 2020 to identify randomized controlled trials (RCTs) evaluating the performance of VBNA compared with an NVBNA group. Results were expressed as risk ratio (RR) or mean difference (MD) with accompanying 95% confidence interval (CI). Results: Six RCTs with 1626 patients were included. The overall diagnostic rate was similar in the VBNA (74.17%) and NVBNA (69.51%) groups, with risk ratio of 1.07 (95% CI: 0.98–1.17). However, in the VBNA group, the total examination time was significantly shorter (MD = −3.94 min, 95% CI: −6.57 to −1.36; p = 0.003) than in the NVBNA group. VBNA had superior diagnostic yield than NVBNA for PPLs ⩽ 20 mm (RR = 1.18, 95% CI: 1.05–1.32). In addition, diagnostic yield according to nature of lesion, lesion location in the lung lobe, distance from the hilum, bronchus sign and complications were similar between VBNA and NVBNA groups. Conclusion: VBNA bronchoscopy did not increase overall diagnostic yield in patients with PPLs compared with NVBNA bronchoscopy. The superiority of VBNA over NVBNA was evident among patients with PPLs ⩽ 20 mm. Future multicenter RCTs are needed for further investigation. The reviews of this paper are available via the supplemental material section.